Pathophysiology and Complications of Diabetes Mellitus - Oguntibeju, Oluwafemi O. (IntechOpen, 2012)
Diabetes mellitus is a complex, progressive disease, which is accompanied by multiple complications. It is a metabolic disorder of the endocrine system and listed among the most common disorders in both developed and developing countries. It has a global metabolic epidemic and it is estimated that the number of people affected by the disease will rise from the current 150 to 230 million by 2025. Hyperglycaemia is a characteristic feature of diabetes mellitus and chronic hyperglycaemia could lead to long-term complications in the eyes, kidneys, nerves, heart and blood vessels. Interestingly, this book examines the pathophysiology and selected complications in diabetes mellitus.